Using Memrise as a Technology-Based Learning Media in Improving Students' Speaking Skills - Subhan, Roni; Syariatin, Nur; Ihsan, Rodiyal; Musdalifah, Andi; Waruwu, Yaredi (Journal International of Lingua and Technology, 2024)
This study aims to investigate the effectiveness of using technology-based learning platforms, especially Memrise, to improve students' speaking skills. At a time when technology continues to develop rapidly, the use of digital learning platforms is becoming increasingly important in efforts to improve student learning outcomes. This study involved students as participants in a learning environment to conduct experiments using Memrise as a learning medium to develop speaking skills. This study applies a class action research approach with a qualitative approach. Data collection was carried out through observation, interviews, and documentation review of the learning activities carried out by students using Memrise. The results of the study show that the use of Memrise as a technology-based learning medium is effective in increasing student motivation, developing speaking skills, and increasing active participation in the learning process. This platform provides an interactive environment that supports independent and collaborative speaking practice. The results of this study have important implications for the design of learning strategies that focus on developing speaking skills through the use of technology. These findings also highlight the importance of integrating technology into education to address communication challenges in everyday life. So, the use of Memrise as a technology-based learning media can be seen as a suitable solution to improve students' speaking skills.